Current Topics in Complement II - Lambris, John D.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2008)
Complement has long been regarded as a pivotal effector arm of the innate immune response, eliciting important immunoregulatory functions in the context of inflammation and also serving as a vital link between the innate and adaptive immune response. In the post-genomic era, our knowledge of the innate immune system is enriched by findings that point to novel functions that do not strictly correlate with immunological defense and surveillance, immune modulation or Inflammation. Several studies indicate that complement proteins exert functions that are either more complex than previously thought, or go well beyond the innate immune character of the system. The advent of high-throughput platforms for genome and proteome-wide profiling, together with the enormous amount of raw genetic information that has accumulated in the databases, have stirred new expectations in biomedical research. They have led complementologists to revisit established biological systems, such as the complement system, from a global and integrative perspective. Complement research is now faced with the challenge of trying to integrate isolated biochemical pathways into complex gene and protein regulatory circuits. In this respect, scientists from around the world convened at the Fourth Aegean Conferences Workshop on Complement Associated Diseases, Animal Models, and Therapeutics (June 10-15, 2007), to discuss recent advances in this fast evolving field. This volume represents a collection of topics on the “novel” functions of complement, patho-physiology, protein structures, design of complement inhibitors, and complement assays discussed during the conference.
Adipokines and the Immune System: An Adipocentric View -- The Role of Complement in Stroke Therapy -- Food Intake Regulation by Central Complement System -- A Pivotal Role of Activation of Complement Cascade (CC) in Mobilization of Hematopoietic Stem/Progenitor Cells (HSPC) -- Regulation of Tissue Inflammation by Thrombin-Activatable Carboxypeptidase B (or TAFI) -- Interaction Between the Coagulation and Complement System -- Platelet Mediated Complement Activation -- Adrenergic Regulation of Complement-Induced Acute Lung Injury -- Ficolins: Structure, Function and Associated Diseases -- Complement Factor H: Using Atomic Resolution Structure to Illuminate Disease Mechanisms -- Role of Complement in Motor Neuron Disease: Animal Models and Therapeutic Potential of Complement Inhibitors -- The Role of Membrane Complement Regulatory Proteins in Cancer Immunotherapy -- Role of Complement in Ethanol-Induced Liver Injury -- Immune Complex-Mediated Cytokine Production is Regulated by Classical Complement Activation both In Vivo and In Vitro -- Subversion of Innate Immunity by Periodontopathic Bacteria via Exploitation of Complement Receptor-3 -- Staphylococcal Complement Inhibitors: Biological Functions, Recognition of Complement Components, and Potential Therapeutic Implications -- Human Astrovirus Coat Protein: A Novel C1 Inhibitor -- Hypothesis: Combined Inhibition of Complement and CD14 as Treatment Regimen to Attenuate the Inflammatory Response -- Targeting Classical Complement Pathway to Treat Complement Mediated Autoimmune Diseases -- Compstatin: A Complement Inhibitor on its Way to Clinical Application -- Derivatives of Human Complement Component C3 for Therapeutic Complement Depletion: A Novel Class of Therapeutic Agents.
Keywords: Immunology; Microbiology; Infectious diseases; Pathology; Immunology; Microbiology; Infectious Diseases; Pathology